Gravity constraints on extension and magmatism in the northernmost Rio Grande rift, northern Colorado - Espinoza Celi, Jorge Andrés, author; Harry, Dennis, advisor; Schutt, Derek, committee member; Kanno, Yoichiro, committee member (Colorado State University. Libraries, 2025)
The Rio Grande Rift (RGR) is a north-trending belt of extensional basins extending from southern New Mexico to central Colorado, where its physiographic expression ends. Opening of the RGR initiated in the late Oligocene forming a series of rift basins linked by accommodation zones where the amount of extension increases southward. This thesis tests the hypothesis that RGR related extensional processes can be found further north in Colorado where basins such as Middle Park, North Park and Sand Wash are located. In this region, extensional features are more broadly distributed up to the southern edge of the Wyoming craton near the Wyoming state border. To evaluate the hypothesis, gravity data from the PACES dataset was complemented by 192 new gravity measurements. This data was used to calculate a Free Air Anomaly map and construct a forward gravity model to constrain lithosphere and upper asthenosphere density structure. The results are illustrated along three E-W oriented cross sections cutting Middle Park, the Rabbit Ears Range and North Park. The observed gravity field along these profiles correlate with the topography, showing higher gravity values over the Park Basins and the Front and Park Ranges. Lower gravity values are observed west of the Park Basins in the Sand Wash Basin and Uinta Basin areas. The calculated gravity field from the density model reveal, large amplitude, long wavelength gravity misfits showing a gravity overestimation in the Park Basins region and underestimation near the Colorado-Utah state border. These misfits were reduced by adding igneous features at various depths within the lithosphere and lateral density and thickness variations in the crust. Beneath the Park Basins region, the igneous features in the forward model are smaller and more felsic toward the north which supports lithospheric thinning and decompression melting with more advanced extension towards the south consistent with the southward increase in RGR extension observed in its main rift basins. The results correlate with seismic evidence from previous studies showing shallowing in the lithosphere-asthenosphere boundary and low Vp and Vs in northern Colorado. The results point to the northern Colorado region being part of the RGR system but at a less mature stage of rifting compared to the main RGR rift basins found further south.
Keywords: extension; gravity; Rio Grande rift; forward modelling; Colorado; IGMAS